Horace’s Epistles, Wieland and the Reader - Curran, Jane V. (MHRA Texts and Dissertations, 1995)
Wieland’s translations of Horace’s Epistles, neglected until recently, demonstrate his skill in overcoming the bipolar relationship implied in the very idea of translation. Thanks to a strong, cosmopolitan fellow-feeling with the ancient poet, Wieland made judicious editorial choices in the areas of diction, prosody, layout, typography and scholarly apparatus. This most flexible of translators avoided collapsing the distinctions between his own world and Horace’s, and achieved true communication with Horace, while simultaneously drawing the contemporary German reader into the dialogue. Translation techniques employed by Wieland’s contemporaries are also discussed here, as well as Horace’s reception during the period, and the tensions between originality and imitation, and between ancient hexameter and modern metres. This book, originally published in paperback in 1995 under the ISBN 978-0-901286-47-5, was made Open Access in 2024 as part of the MHRA Revivals programme.